Training interventions in job-skill development - Gardner, James E. (Reading, Mass. : Addison-Wesley, 1981)
The author in an earlier book (Helping Employees Develop Job Skill, published by the Bureau of National Affairs in 1976), made a number of points about the learning process as it relates to industrial jobs and about the developmental nature of that process. Thus the ground was laid in that volume, he felt, for an examination of how we might put the principles and techniques to use in the training of production employees.
Includes index.
Includes bibliographical references and index.
hza 26/07/2018
Loans
Keywords: Employees